2014
DOI: 10.2134/agronj2013.0307
|View full text |Cite
|
Sign up to set email alerts
|

Soil, Water, and Nutrient Management Options for Climate Change Adaptation in Southern Africa

Abstract: Climate change and food insecurity are the two major challenges for humanity in developing countries. Drawing lessons from numerous research studies from southern Africa and regions on other continents, this review discusses possible interventions for climate and ecological change adaptation using improved water management, soil fertility amelioration, and intensive crop management options. is review and the proposed framework should provide useful information for improving agricultural policy in southern Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The increase in green manure legumes yield following basal fertilization suggest that soil supply of NPS was improved by the mineral fertilizer. Nitrogen and P are major limiting nutrients in Malawi (Kadyampakeni, 2014) as in other southern African countries (Kanonge et al , 2015) and previous studies have shown that P improves growth and N 2 fixation of legumes (Cassman et al , 1993; Whitbread et al , 2004). Soils in Malawi, as in other parts of southern Africa (Grant and Rowell, 1976), are low in S (Sakala and Mhango, 2003; Weil and Mughogho, 2000) and green manure legume yields could have increased in response to improved soil S supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in green manure legumes yield following basal fertilization suggest that soil supply of NPS was improved by the mineral fertilizer. Nitrogen and P are major limiting nutrients in Malawi (Kadyampakeni, 2014) as in other southern African countries (Kanonge et al , 2015) and previous studies have shown that P improves growth and N 2 fixation of legumes (Cassman et al , 1993; Whitbread et al , 2004). Soils in Malawi, as in other parts of southern Africa (Grant and Rowell, 1976), are low in S (Sakala and Mhango, 2003; Weil and Mughogho, 2000) and green manure legume yields could have increased in response to improved soil S supply.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of positive responses to inorganic fertilizer by some green manure legumes species such as cowpea have also been reported in another study conducted in southern Africa under conventional agriculture (Jeranyama et al , 2000). Soils with moderate to high initial NPK levels often give poor crop yield responses to inorganic fertilizer (Kadyampakeni, 2014) and lack of responses to fertilizer at DTC, UZ and Monze are possible as the soils at these sites are not highly degraded. Even maize grown in the green manure legumes phase at the three sites did not respond to basal fertilization at half and full rates, further highlighting the fact that soil supply of NPK was adequate for growth of the species tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from individual shared elements that link up individual soil, food, and water systems (Figure 1), several studies have also examined this soil-food-water nexus in the context of sustainable development. For example, Love et al (2006) and Kadyampakeni (2014) argued that SDG 2 (food security) can be addressed through increased access to fertilizers, technology transfer and training, soil-water conservation methods, mixed livestock and arable agriculture, and farm diversification. It is notable that each of these proposed interventions involves corelationships between different elements of physical and human systems, and that these relationships are not straightforward or without impact.…”
Section: The Soil-food-water Nexusmentioning
confidence: 99%
“…Sustainable provision of food in SSA faces challenges of increasing population and changing climate. Agricultural soils are vulnerable to degradation because of rapid carbon turnover (3-5 times faster than temperate regions) and poor nutrient retention, so recycling of organic resources is essential to replenish carbon and plant nutrients [64,65,66] and avoid adverse impacts on yield, water storage and erosion resistance [67]. Inorganic fertiliser use is beyond the reach of many households [68].…”
Section: Impact On Food Provisionmentioning
confidence: 99%